Generalizations of Sherman’s inequality via Fink’s identity and Green’s function - Ivelic, Bradanovic S.; Latif, M. A.; Pečarić, J. E. (Ukrains’kyi Matematychnyi Zhurnal, 2018)
New generalizations of Sherman’s inequality for $n$-convex functions are obtained by using Fink’s identity and Green’s function. By using inequalities for the Chebyshev functional, we establish some new Ostrowski- and Gruss-type inequalitiesrelated to these generalizations.